PENGARUH BUDAYA ORGANISASI TERHADAP SIKAP KEWIRAUSAHAAN SISWA PADA PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) TEMA KEWIRAUSAHAAN DI SMPN KOTA YOGYAKARTA - Setiani, Puji; Rifqi, Ainur (Edu Learning : Journal of Education and Learning, 2024)
This research discusses the description of organizational culture and entrepreneurial attitudes at SMPN Kota Yogyakarta as well as the influence of organizational culture on the entrepreneurial attitudes of education staff and students. The grand theory used in this research is the organizational culture theory from Luthans and the entrepreneurial attitude theory from Schumpeter, J. A. The research method uses quantitative methods using parametric statistics Simple Linear Regression Analysis Test. The sample in this research was 87 educational staff educators and 210 students implementing the project to strengthen the profile of Pancasila students (P5) with the theme of entrepreneurship at SMPN Kota Yogyakarta. The location of this research was carried out at 4 SMPN Yogyakarta City. Based on the results of data analysis, it shows that the level of organizational culture of educational staff educators (PTK) has an average of 69.14 and students have an average of 71.70 and the level of entrepreneurial attitude of educational staff educators (PTK) has an average of 92.55 and students had an average of 84.00. There is a positive and significant influence on these two variables, namely organizational culture on educational staff (PTK) of 0.197 or 19.7% and students of 0.533 or 53.3%. This score can be said to be quite good, even though there are other variables outside the research model that influence the entrepreneurial attitudes of education staff (PTK) educators and students. This is again confirmed by the results of regression analysis calculations where a significance value of 0.000 < 0.05 is obtained, which can be concluded that organizational culture (X) influences the entrepreneurial attitude (Y) of educational staff (PTK) educators and students implementing student profile strengthening projects. Pancasila (P5) entrepreneurship theme at SMPN Yogyakarta City.